Perinatal HIV and Neurodevelopment - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
The natural history of HIV disease and neurodevelopmental disorders in 21 perinatally infected children were examined in a collaborative prospective study sponsored by the National Institute of Child Health & Human Development, Rockville, MD.